Mesoporous silica polymer nanocomposites encapsulated with polyphosphoric acid for the synthesis of β-amino carbonyl compounds under environmental benign conditions. (3rd February 2015) - Sachdev, Divya; Dubey, Amit; Wilson, G. Robin; Sharma, Ankita
Abstract : Hydrophobic polymer functionalized SBA-15 was impregnated with polyphosphoric acid. Polymer composites SAR displays a crucial role in the selective synthesis of Mannich base. Abstract : Mesoporous silica–polymer nanocomposites (SBA/PS) synthesized via wet impregnation method were functionalized by mild polyphosphoric acid (PPA) for catalytic applications. The catalysts were characterized and analysed by powder X-ray diffraction (PXRD), solid state nuclear magnetic resonance ( 31 P-SSNMR), N2 -adsorption–desorption isotherm, Fourier transform-infrared (FT-IR), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HR-TEM) and thermogravimetric analysis (TGA/DTA). The catalytic studies of a multicomponent Mannich reaction was conducted wherein the hydrophobic nature of these nanocomposites showed an enhancement in the product activity and selectivity of β-amino carbonyl (Mannich base) compounds. The probable reaction mechanism elucidates the role of well-distributed active sites on the hydrophobic surface and the stability of the catalyst for good catalytic activity.